Instructions for the Use of the Computer Program to Obtain the Diagnosis of Bone Age (by Hand and Tarsus) and Prediction of Adult Size of Spanish Child - Bernardo Ebrí Torné; Verde, María Inmaculada Ebrí (Research Developments in Medicine and Medical Science Vol. 5, 2023)
In this article, the authors detail the necessary instructions to proceed correctly to interpret the computer program to calculate the bone age and prognosis of adult size of the child under study. This program is free download from the website of the Illustrious College of Medical of Zaragoza (Spain) https://www.comz.org/maduracion-osea Once downloaded on the computer, the practical doctor: radiologist, pediatrician, endocrine or researcher, from the hospital intranet, he will be able to perform the appropriate radiological measures of left hand and Tarsus, as detailed in the attached schemes and figures. When introducing them to the program's computer window, together with the size of the child and parents, the diagnosis of the child's bone age and the prognosis of their adult size can be obtained. Thus, it will be possible to know if the bone age is normal, advanced or delayed, and can be required in these cases to expand the study by other procedures as analytics. The database of children who have served to prepare this program has been obtained from the Spanish Longitudinal Series of the Andrea Prader Center.